Agricultural productivity in Kenya: 2000-2020 - Nin-Pratt, Alejandro (International Food Policy Research Institute, 2023)
Agriculture is key to economic growth and poverty reduction in Kenya as it plays a pivotal role in employment creation, food security, exports, and sustainable development. In 2019, it directly contributed 22.7 percent of GDP, accounted for 20.9 percent of total exports, and generated 43.3 percent of employment (Chapter 2). The sector is thus not only an important driver of Kenya’s economy but also the means of livelihood for many Kenyan people. Given the economic and social importance of agriculture in Kenya, policies have revolved around the main goal of increasing productivity and incomes, especially for smallholders, to enhance food security and equity, with an emphasis on production intensification, commercialization, and environmental sustainability (Alila and Atieno 2006). In this context, the declining perfor mance of the sector measured in terms of its growth has been a major concern for policymakers.